2013
DOI: 10.1371/journal.pone.0083903
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase HDAC4 Regulates Long-Term Memory in Drosophila

Abstract: A growing body of research indicates that pharmacological inhibition of histone deacetylases (HDACs) correlates with enhancement of long-term memory and current research is concentrated on determining the roles that individual HDACs play in cognitive function. Here, we investigate the role of HDAC4 in long-term memory formation in Drosophila. We show that overexpression of HDAC4 in the adult mushroom body, an important structure for memory formation, resulted in a specific impairment in long-term courtship mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
95
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 79 publications
8
95
0
Order By: Relevance
“…The truncated form of HDAC4 also caused cognitive deficits in mice, which were associated with reduced expression of plasticity-related genes (Sando et al 2012). We also demonstrated that overexpression of HDAC4 in Drosophila resulted in impaired LTM and recruited MEF2 to discrete foci within nuclei (Fitzsimons et al 2013). Taken together, these data indicate that when in the nucleus, HDAC4 has the capacity to repress expression of plasticity-related genes, which correlates with memory impairment (Sando et al 2012); however, it also plays a promemory role, as evidenced by the memory impairments that result from reduction of HDAC4 in the adult brain Fitzsimons et al 2013).…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…The truncated form of HDAC4 also caused cognitive deficits in mice, which were associated with reduced expression of plasticity-related genes (Sando et al 2012). We also demonstrated that overexpression of HDAC4 in Drosophila resulted in impaired LTM and recruited MEF2 to discrete foci within nuclei (Fitzsimons et al 2013). Taken together, these data indicate that when in the nucleus, HDAC4 has the capacity to repress expression of plasticity-related genes, which correlates with memory impairment (Sando et al 2012); however, it also plays a promemory role, as evidenced by the memory impairments that result from reduction of HDAC4 in the adult brain Fitzsimons et al 2013).…”
mentioning
confidence: 59%
“…We also demonstrated that overexpression of HDAC4 in Drosophila resulted in impaired LTM and recruited MEF2 to discrete foci within nuclei (Fitzsimons et al 2013). Taken together, these data indicate that when in the nucleus, HDAC4 has the capacity to repress expression of plasticity-related genes, which correlates with memory impairment (Sando et al 2012); however, it also plays a promemory role, as evidenced by the memory impairments that result from reduction of HDAC4 in the adult brain Fitzsimons et al 2013).Here, we sought to increase understanding of the molecular mechanisms through which HDAC4 regulates memory via a two-pronged approach. First, in order to investigate whether the memory deficits we observed following overexpression of HDAC4 were accompanied by alterations in gene expression, we performed RNA sequencing (RNAseq) on heads of flies that overexpressed HDAC4 in the adult brain; however, very few changes were found, suggesting that wildtype (WT) HDAC4 elicits limited transcriptional effects.…”
mentioning
confidence: 62%
See 3 more Smart Citations